Relational antecedents of innovation in family firms: The complexity role of non-family employees' commitment - Jorge-Humberto Mejía-Morelos; Luis-Felipe Cisneros-Martinez; Christian Keen; Valeriano Sanchez-Famoso (European Journal of Family Business (EJFB), 2020)
A better understanding of the relational antecedents of innovation in family firms is central to explaining their long-term success and survival. Our study proposes an original model that shows that the internal social capital of non-family members does not always foster innovation directly as existing theory suggests, but through their organizational commitment. These results differ across the different dimensions of organizational commitment. Therefore, our study challenges existing thinking on commitment studies by offering theoretical grounding and empirical evidence that neglected dimensions of commitment have a crucial intermediate role in the relationship between internal social capital and innovation in family firms.
Keywords: L20; L26; O32; 650; Family business; Non-family employees; Social capital; Innovation; Commitment